Improving Student Recent Writing Skills Using the Project Based Learning (PJBL) Model For Class XI MIPA 3 SMA Negeri 6 Madiun - Lafitri, Wika Syabriyanti; Suryatmoko, Agus; Suharto, V. Teguh (International Journal Corner of Educational Research, 2023)
This study aims to solve problems regarding students' low writing skills. Through the Project Based Learning learning model, it is hoped that it will be able to improve students' writing skills, especially in the Indonesian subject of review text material. This research is included in the type of Class Action Research (CAR) using the model from Kemmis and Mc. Taggart. The subjects of this study were 35 students of class XI MIPA 3 of SMA Negeri 6 Madiun. The approach in this study uses a qualitative description. Meanwhile, data collection techniques were carried out using test and non-test instruments in the form of observation sheets. Analysis of the data for each cycle showed that in cycle 1 student completeness only reached 11.42% (not yet achieved) then in cycle 2 it increased to 85.71% (has been achieved). In addition, the non-test results showed that the effectiveness of using the Project Based Learning learning model in cycle 1 was 27.5% (poor) and increased in cycle 2 to 90% (very good).